Performance improvement of synchronous permanent magnet generator for oscillating water column (OWC) wave energy converter - Nallagowden, P. (Institute of Electrical and Electronics Engineers Inc., 2017)
This paper presents the performance analysis and improvement of electric power generation for Oscillating Water Colum (OWC) wave energy converter using Finite Element Analysis (FEA). The existing power take-off system in OWC is based on induction machines which not only suffer from poor efficiency but require significant maintenance also. Conversely, synchronous permanent magnet (PM) generators offer numerous advantages and are adopted largely in wave energy conversion systems. This work proposes a synchronous permanent magnet (PM) generator with segmented magnets which enhances the electromagnetic characteristics and improves the efficiency as compared to conventional generators. In order to determine electromagnetic performance FEA has been carried out, two modes; no-load and full-load operations are analyzed in detail. The proposed synchronous permanent magnet (PM) generator is compared with conventional and the results such as; magnetic flux density, induced-voltage and flux linkage along with efficiency evaluation are presented. © 2016 IEEE.